Periodic flow of a second grade fluid due to the disks executing non-torsional oscillations in an orthogonal rheometer under the influence of a magnetic field - Ersoy, H. Volkan (Zielona Góra: Uniwersytet Zielonogórski)
The present paper studies the periodic flow of a second grade fluid generated by non-torsional oscillations of the disks rotating in the eccentric form under the application of a magnetic field. Subsequent to the rotational motion of the disks at a common angular velocity about two vertical axes, they perform oscillations horizontally in a symmetrical manner.
Keywords: magnetohydrodynamics; non-torsional oscillation; orthogonal rheometer; periodic flow; second grade fluid